2023
DOI: 10.1101/2023.06.23.546257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type IV-A3 CRISPR-Cas systems drive inter-plasmid conflicts by acquiring spacersin trans

Fabienne Benz,
Sarah Camara-Wilpert,
Jakob Russel
et al.

Abstract: Type IV-A CRISPR-Cas systems are primarily encoded on plasmids and form multi-subunit ribonucleoprotein complexes with unknown biological functions. In contrast to other CRISPR-Cas types, they lack the archetypical CRISPR acquisition module and encode a DinG helicase instead of a nuclease component. Type IV-A3 systems are carried by large conjugative plasmids that often harbor multiple antibiotic-resistance genes. Although their CRISPR array contents suggest a role in inter-plasmid conflicts, this function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…In addition, regardless of sequence divergence, any conditions that physically separate two intracellular genomes but allow mixing of their encoded proteins present the potential to involve homing endonuclease–mediated interference competition if one of the genomes acquires a homing endonuclease. The relative fitness advantage we observed that is provided by a weaponized homing endonuclease could influence any intracellular genetic competition, including those arising between plasmids ( 50 ), viruses, and hosts.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, regardless of sequence divergence, any conditions that physically separate two intracellular genomes but allow mixing of their encoded proteins present the potential to involve homing endonuclease–mediated interference competition if one of the genomes acquires a homing endonuclease. The relative fitness advantage we observed that is provided by a weaponized homing endonuclease could influence any intracellular genetic competition, including those arising between plasmids ( 50 ), viruses, and hosts.…”
Section: Discussionmentioning
confidence: 95%
“…This mechanism is especially important in the evolution of viruses due to their constant competition through co-infection 51,52 and rapid rates of viral replication where even small selective advantages are quickly amplified over time. More broadly, this new understanding of the fitness advantage provided by weaponized mobile introns could come into play under the right circumstances for any intracellular genetic competition, including between plasmids 62 , viruses, and hosts.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of work highlights the frequent co-option of CRISPR-Cas systems and their components by diverse MGEs 4 . Some specific CRISPR-Cas associations with MGEs have been characterized in detail, including crRNA-guided transposition 11,12 , transcriptional repression 13 and inter-viral 14 and inter-plasmid 15,16 conflicts, but others are poorly understood. An intriguing case is the bioinformatic identification in viral genomes of solitary repeat units (SRUs), which are often immediately downstream of a predicted promoter and not associated with cas genes 4 .…”
mentioning
confidence: 99%